Pengaruh Media Kartu Prosedur Kreatif (KPK) terhadap Peningkatan Keterampilan Menulis Teks Prosedur Peserta Didik SD - Farhan Iqbal Pratama; Haryadi Haryadi; Bernadus Wahyudi Joko Santoso (FONDATIA, 2026)
Writing procedural texts requires logical and systematic thinking skills, yet it remains challenging for elementary school students, who often struggle to sequence steps correctly and apply appropriate linguistic conventions. This study aimed to examine the significance of the effect of creative procedure card (KPK) media in improving elementary students’ procedural text writing skills. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design involving 21 students selected through random sampling. Data were collected through a performance test of procedural text writing administered as both pretest and posttest, then analyzed using normality tests, homogeneity tests, ANOVA, and t-tests. The results showed that KPK media had a significant effect on procedural text writing skills, with F_value > F_critical (29.181 > 4.60), and that there was a difference in students’ abilities before and after the use of KPK media, as indicated by t_value > t_critical (54.529 > 1.753). KPK media contributed 67.6% to the improvement of procedural text writing skills, demonstrating that its use is effective in optimizing elementary school students’ ability to write procedural texts.